Apical left ventricular hypertrophy and mid-ventricular obstruction in Fabry disease - Cianciulli, Tomás F. (2015)
We report the case of a rare cardiac presentation of Fabry disease. Although concentric left ventricular hypertrophy is a major cardiac finding in Fabry disease, there is no case report of dynamic obstruction at mid-left ventricular level. We describe a 59-year-old-woman suffering from a severe form of Fabry disease, mimicking an apical hypertrophic cardiomyopathy with mid-ventricular obstruction. Differentiation of Fabry disease from hypertrophic cardiomyopathy is crucial given the therapeutic and prognostic differences. Fabry disease should always be suspected in an adult, independently of the pattern of left ventricular hypertrophy. Mini-Abstract We report the case of a rare cardiac presentation of Fabry disease. Although concentric left ventricular hypertrophy is a major cardiac finding in Fabry disease, there is no case report of dynamic obstruction at mid-left ventricular level. We describe a 59-year-old-woman suffering from a severe form of Fabry disease, mimicking an apical hypertrophic cardiomyopathy with mid-ventricular obstruction. Differentiation of Fabry disease from hypertrophic cardiomyopathy is crucial given the therapeutic and prognostic differences. Fabry disease should always be suspected in an adult, independently of the pattern of left ventricular hypertrophy.